ISSUES OF DEVELOPING THE DIGITAL ECONOMY IN UZBEKISTAN - Khamrayeva, Sayyora; Ravshanova, Nigora (THE INNOVATION ECONOMY, 2024)
In this article, the problems related to the legal basis of the development of the digital economy in Uzbekistan are based. The important role and importance of the digital economy in the social and economic development of the countries of the world today, as well as the prospects for the development of the digital economy in our country, are highlighted. The implementation of the "Electronic Government" system was focused on effective coordination and the rational use of resources based on a single technological approach, as well as an increase in the efficiency of activities. The directions aimed at the implementation of fundamental reforms for the liberalization and development of the economy, improvement of the business environment, and the increase of the competitiveness of economic sectors have been mentioned. The importance of assessing the level of legal security in the era of digital economy, implementing deep structural changes in economic sectors, accelerating the process of transition to a competitive market economy while forming a high-quality market of goods and services is highlighted.